Inflammasome biology : fundamentals, role in disease states, and therapeutic opportunities - Pelegrin, Pablo (Academic Press, 2022)
Inflammasome Biology: Fundamentals, Role in Disease States, and Therapeutic Opportunities is a complete reference on the role of inflammasomes in health and disease. Sections cover the different types of inflammasomes, including cellular signaling, structural and evolutive aspects, overview the role of inflammasomes in key diseases, microbial infections and human body systems conditions, cover the interplay between Inflammasomes and cell death processes, and discuss current therapeutic opportunities driven by inflammasome research, including targeting, blocking and inhibiting the development of inflammasomes through both synthetic and natural compounds.